THE INFLUENCE OF TOILET TRAINING ON THE INDEPENDENCE OF 5-6 YEAR OLD CHILDREN AT ERWITA EDUCARE CENTER - Gustina, Fatma; Abidin, Zainal; Nurliani, Nurliani; Marzaniatun, Marzaniatun; Feriana, Rina (JURNAL TARBIYAH, 2024)
This research was motivated by the low ability of children to do this toilet training, Toilet training provide a positive impact on child development. examples of the impact of learningtoilet training is to foster self-confidence in children, train and increase children's independence and enable children to discipline themselves. The type of research used is quantitative research, with the research design used is Quasi Experimental, namely Pretest-posttest Control Group.Based on the results of research conducted by researchers using normality, homogeneity and hypothesis tests, it can be concluded that tcount< ttable, until Ha is acceptedand H0 is rejected. The percentage in the banana group (experimental class) of the test results was 32.89% for the pre-test and 68.60% for the post-test. Meanwhile, in the mango group (control class) the results of the test were 32.14% pre-test percentage and 63.75% post-test. From these two data results, it can be concluded that toilet training has an effect on the independence of children aged 5-6 years at the Erwita Educare Center.